Perbandingan Antara Pendekatan Problem Posing Dan Pendekatan Ekspositori Terhadap Prestasi Belajar Matematika Siswa - Nurjannah Nurjannah; Fitriani Fitriani (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2021)
The purpose of this study was to obtain information that learning achievement with a problem-posing approach is better than learning achievement with an expository approach. This research was comparative experimental research. The population in this study were all eighth-grade students at SMP Negeri 2 Kahu. The samples, namely Class VIIIA and VIIIC, were randomly selected from 5 existing classes as the experimental class and the control class. Data were collected by giving a learning achievement test (post-test) to determine the level of student achievement. The data analysis technique was carried out using descriptive statistics and inferential statistics. The results of the descriptive analysis showed that the average score of students in the experimental class was 78.18 with a standard deviation of 13.67, while the average score of students in the control class was 66.19 with a standard deviation of 11.90. The results of inferential statistical data analysis using t-test obtained a p-value of 0.001 < 0.05, so it can be concluded that students' mathematics learning achievement with the problem-posing approach is higher than student achievement with the expository approach.